(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article discusses the role and importance of oral speech in improving the literacy of students, ways to achieve the formation of speech skills in mother tongue and reading literacy classes, and an innovative approach to speech development.